STUDI PADA SIFAT FISIK, MEKANIK, DAN KARAKTERISTIK ANATOMI KAYU KACANG (Strombosia javanica) DI MANDIANGIN, KABUPATEN BANJAR, KALIMANTAN SELATAN - Muhammad Fadhil; Gusti Abdul Rahmat Thamrin; Wiwin Tyas Istikowati (Universitas Lambung Mangkurat, 2020)
The purpose of this study was to determine the physical, mechanical, and characteristics anatomy of kayu kacang (Strombosia javanica) and recommend the suitability of using kayu kacang based on data obtained in this study. The expected benefit of this research is to be able to provide information and preliminary data for industries and communities who want to develop and utilize kayu kacang, so that the use of peanut wood (Strombosia javanica) matches the characteristics it has. The method used is cutting kayu kacang wood sticks with small pieces in several parts that will be processed into sample material physical, mechanical, and characteristics anatomy of kayu kacang. The results showed that kayu kacang trees had class III wood strength and had very short fiber lengths and very short vessel lengths.